Organizational Culture in Public Service Delivery at the Population and Civil Registration Office of Kebumen Regency in 2025 - Monica Shafa Anugrah; Joko Tri Nugraha; Tri Asih Wismaningtyas (Journal of Public Policy, Governance and Local Government, 2026)
Population administration services play a crucial role in governance and in ensuring citizens’ fundamental rights. These services are administered by the Population and Civil Registration Office (Disdukcapil). The effectiveness of service delivery is strongly influenced by organizational culture, which shapes employees’ behavior and work patterns. This study aims to assess the level of organizational culture within Disdukcapil of Kebumen Regency in 2025. This research employs a quantitative method with a descriptive approach. The instrument used is an adapted organizational culture questionnaire consisting of six dimensions: professionalism, management distance, trust among colleagues, regularity, hostility, and integration. The findings indicate that organizational culture within Disdukcapil Kebumen is generally strong, particularly in the dimensions of trust among colleagues, regularity, and integration. Meanwhile, professionalism and management distance fall into the moderate category. The hostility dimension shows a strong score, indicating a relatively harmonious work environment due to its unfavorable measurement scale. However, improvements are still required, particularly in professionalism and management distance. In addition, discrepancies between survey results and actual practices were identified in the regularity dimension. The study recommends strengthening professionalism, improving managerial relationships, enhancing rule consistency, and anticipating potential interpersonal tensions.